Lymphatic Microsurgical Preventive Healing Approach (LYMPHA) for the prevention of secondary lymphedema. Issue 4 (20th October 2019) - Agarwal, Shailesh; Garza, Rebecca M.; Chang, David W.
Abstract: Lymphedema is a chronic, morbid condition in which the upper or lower extremity experiences swelling and fibrosis due to impaired lymphatic clearance. Among breast cancer patients, this condition is primarily attributed to axillary lymph node dissection (ALND) performed for oncologic management. While nonoperative and operative approaches to lymphedema management may be implemented to "manage" this condition, they are typically not curative. Therefore, lymphedema prevention in patients who have undergone ALND is of critical importance. Here, we briefly describe lymphedema and available management strategies, and focus on prevention in patients undergoing ALND using the Lymphatic Microsurgical Preventive Healing Approach (LYMPHA). Currently available clinical and experimental evidence suggests that LYMPHA may provide protection against the development of lymphedema in carefully selected patients. This procedure can serve as an adjunct surgical option for patients at the time of ALND.